Efficiency of the Competition Protection Commission in the Republic of Serbia: Examples from practice - Marjanović, Marijana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
Competition is one of the pillars of a democratic society with a regulated market economy, as it fosters economic growth, innovation, and an improved standard of living. Modern states protect competition not only by establishing an adequate legal and institutional framework but also through the implementation of an active competition policy, since the mere existence of regulations is insufficient without their consistent enforcement. In the Republic of Serbia, the supervision of the implementation of competition protection regulations is entrusted to the Commission for Protection of Competition, whose effectiveness directly affects economic efficiency and overall social welfare. The aim of this paper is to examine the extent to which the Commission fulfills its role in protecting competition by analyzing the legal framework, procedures before the Commission, and concrete cases from practice. The paper identifies key challenges in the Commission’s work and formulates recommendations for improving the regulatory and institutional framework, with the goal of enhancing transparency, efficiency, and alignment with European standards in the field of competition law.